(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Modern diets are often high in fructose, and this has been associated with increased inflammation and oxidative stress. Herbal remedies like Paxherbal bitters have been suggested as possible remedies. This study aims at determining if the co-administration of Paxherbal bitters could prevent the inflammation and oxidative stress, which occurs when male Wistar rats are fed a high fructose diet. Twenty male Wistar rats, approximately 200g each, were divided into four groups: the control, high fructose diet with fructose water (HFD+FW), HFD+FW with Atorvastatin, and HFD+FW with Paxherbal bitters, groups. After a 28-day experimental period, blood samples were assessed for high-sensitive C-reactive protein (HsCRP), malondialdehyde (MDA), and total antioxidant capacity (TAC), using standard methods. Statistical analysis was done using the SPSS-20 package. Results has shown that rats on the high fructose diet, displayed significantly (P<0.05) elevated HsCRP (0.63±0.04 mg/dl) and MDA (0.32±0.01 µM) levels, compared to control levels (0.27±0.01 mg/dl; 0.10±0.01 µM). Both Atorvastatin and Paxherbal bitters significantly (P<0.05) prevented the elevation of HsCRP, while only Paxherbal bitters significantly (P<0.05) prevented the increase in MDA level (0.13±0.02 µM) compared to the level seen in the HFD+FW group. The high fructose diet significantly (P<0.05) reduced the TAC in the rats, but Atorvastatin and Paxherbal bitters preserved the TAC (0.38±0.03 µmol/ml; 0.49±0.04 µmol/ml) of their respective groups compared to that of the negative control group (0.21±0.06 µmol/ml). This study shows that Paxherbal bitters prevented the inflammation and oxidative stress induced by a high fructose intake, suggesting its co-administration, has some preventive therapeutic role.